Pengukuran Kontribusi Komponen Teknologi pada Kelompok Tani Girisenang - Souw, Antonius; Supyandi, Dika (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Technology has an crucial role in enhancing competitiveness and production efficiency, including in the agricultural sector. The Girisenang farmer group, an organization engaged in farming and coffee processing in Bandung Regency, faced challenges in utilizing technology to improve production and productivity. Despite having supportive resources such as extensive land and a large number of members, the adoption of technology was not optimal, leading to production instability. This study aimed to determine the intensity value of technology contribution and assess the contribution of technology components within the Girisenang farmer group. A qualitative method with a case study research techcnic was applied, utilizing technometric analysis to evaluate each technology component. The results showed that the technology component contribution coefficient for technoware had the lowest value, followed by orgaware, inforware, and humanware. The overall technology component contribution coefficient indicating that the technology used by the Girisenang farmer group fell into the semi-modern sophistication category with a moderate classification level.